Infekční artritidy nativních kloubů u dospělých: výskyt v našem souboru pacientů a doporučení antibiotické léčby - Musil, D; Chrdle, A; Horníková, M; Balejová, M; Klouda, J; Pertlíček, J; Trnka, T (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2021)
PURPOSE OF THE STUDY The purpose of the study is to analyse the number of adult patients treated in our department for native joint septic arthritis and to outline guidelines for antibiotic therapy. MATERIAL AND METHODS From the beginning of 2003 to the end of 2020, a total of 36,342 surgeries were performed at our department. We retrospectively reviewed and analysed all surgeries for native joint septic arthritis (a total of 538 surgical interventions). The study included all adult patients who were operated for native joint septic arthritis in our department in 2003-2020. We included all revision surgeries for ongoing infection (excluding the management of post-infectious findings) as well as all operations performed in patients with multiple joint involvement. Based on the analysis of our data and review of published guidelines for antibiotic treatment of septic arthritis, we have outlined our own antibiotic therapy guidelines for the treatment of native joint septic arthritis. RESULTS From 2003 to 2020 we performed a total of 36,342 surgeries, of which 538 (1.5%) in 461 patients was indicated for native joint septic arthritis. The cohort consisted of 292 men (63%), who underwent 344 surgeries, and 169 women, in whom 194 surgeries were performed. The mean age of patients irrespective of the arthritis location was 62.4 years. Altogether, 19 patients (4.1%) suffered from multi-joint arthritis. The most frequently operated joint was the knee with 252 (54%) patients and 300 surgeries (56%), followed by the shoulder with 68 (14.7%) patients and 78 (14.5%) surgeries, the hip with 38 (8.2%) patients and 42 surgeries (8%), the carpal with 30 (6.5%) patients and 35 (6.5%) surgeries, the ankle with 25 patients (5.4%) - 31 (6%) surgeries, the small finger joints with 22 (4.75%) patients and 23 (4%) surgeries, the elbow with 14 (3%) patients and 14 (2.6%) surgeries, the sternoclavicular joint with 9 (1.9%) patients and 12 (2.2%) surgeries and the acromioclavicular joint with 3 patients and 3 (0.5 %) surgeries, respectively. DISCUSSION The management of septic arthritis relies heavily on early diagnosis, early surgical intervention and adequate antibiotic therapy. The diagnostic process and surgical treatment have their specifics related to the affected location, therefore, respective guidelines will be published separately for each location including the results. On the other side, antibiotic management is not dependent on the location and therefore the guidelines are included in this first analysis septic arthritis in the whole cohort. CONCLUSIONS Septic arthritis in adults in an ongoing issue with rising incidence. Early diagnosis, urgent and adequate surgical treatment, and optimal antibiotic therapy are preconditions for successful outcome. Key words: native joint septic arthritis, incidence, antibiotic therapy, guidelines.
Keywords: Humans; lidé středního věku; Female; dospělí; lidé; antibakteriální látky; Adult; Knee Joint; ženské pohlaví; Anti-Bacterial Agents; Male; Middle Aged; Retrospective Studies; incidence; Incidence; Arthritis, Infectious; retrospektivní studie; mužské pohlaví; infekční artritida; kolenní kloub